Penerapan Pendekatan Pembelajaran Saintifik Berbantuan Media Audio Visual Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas V Semester I Sekolah Dasar Triamerta Tahun Pelajaran 2020/2021 - Luh Putu Dewi Primayanti; Putu Yulia Angga Dewi (STAHN Mpu Kuturan Singaraja, 2021)
The Corona Virus (COVID-19) pandemic has had a huge impact on the world of education in Indonesia. To anticipate the transmission of the Corona Virus, the government has taken a policy of maintaining distance (social distancing, physical distancing, to large-scale restrictions (PSBB). Another policy taken by the government is that students study from home so they stay at home (Stay At Home). make the education sector from PAUD / Kindergarten to Higher Education stop the face-to-face learning process. Instead, the learning process is carried out online which can be done at each student's home. Based on the results of research and discussions about the application of a scientific approach assisted by audio-visual media, it can be concluded that it was concluded that the application of a scientific approach assisted by audio-visual media could improve student learning outcomes in class V. SD Triamerta's average student learning outcomes increased from 74.3 in the first cycle to 86.9 in the second cycle